ANALISIS SEKTOR-SEKTOR UNGGULAN KABUPATEN DEMAK - Hendrianto Sundaro (Program Studi Perencanaan Wilayah dan Kota, Fakultas Teknik, Universitas Semarang, 2022)
This study aims to identify the leading sectors in Demak Regency. The research objective are: 1) Knowing the basic and non-basic sectors . 2) Knowing whether there is a shift in the regional economic structure during the 2016-2020 period by looking at the regional components. 3) Knowing the typology of economic sectors. The method used in this study is a quantitative method. The data needed in the form of secondary data, namely PDRB data for Demak Regency in 2016-2020 and PDRB data for Central Java Province in 2016-2020. The analysis was carried out using Location Quotion (LQ) analysis, Klassen Typological Analysis, Shift Share analysis and compilation analysis to obtain a relative ranking of the leading sectors in Demak Regency.The Results of the analysis provide information that have been identified. First rank (Leading Sector) namely the Trade Sector, Water Supply Sector, Waste Management, Waste and Recycling Sector, Education Services Sector, Second Rank (Potential Sector) Processing Industry Sector, Sector Construction, Information and Communication Sector, Financial and Insurance Services Sector, Real Estate Sector, Health Services Sector and Social Activities. Sector providing accommodation and food and drink, Other service sectors. Ranked third (Developing Sector), Agriculture, forestry and fisheries sector, electricity and gas supply sector, transportation and warehousing sector, corporate services sector, government administration sector, mining and quarrying sector.